The crop-animal systems research network (CASREN) - Devendra, C.; Pezo, Danilo A. (International Livestock Research Institute, 2002)
This paper focuses on the background, approaches, and progress made over the last three years by the Crop-Animal Systems Research Network (CASREN) project carried out by ILRI in partnership with national agricultural research systems (NARS) in China, Indonesia, Philippines, Thailand and Vietnam. Topics of discussion include research and development activities; strengthening research capacity of NARS partners; and monitoring and evaluation. The paper ends with an outline on what is next for the CASREN project.